Analisis Fanatisme dan Loyalitas Suporter pada Keputusan Pembelian Merchandise Klub PSMS Medan - Rizky Syahputra; Hafiza Adlina; Onan Marakali Siregar (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study analyzes the role of supporter fanaticism and loyalty in influencing the purchase decisions of official PSMS Medan merchandise. A qualitative descriptive method was employed through in-depth interviews, observation, and documentation, supported by secondary data from literature studies. The results show that fanaticism is reflected in emotional attachment, active involvement, long-term support, and social environmental influences. Supporter loyalty appears in consistent attendance at matches, following games, discussing the club, and repeated purchases of official merchandise. Purchase decisions are influenced by product type, design/form, and quantity, while also considering financial capability. Overall, fanaticism shapes emotional bonding, whereas loyalty drives repeated purchasing behavior; both contribute significantly to merchandise purchasing. These findings highlight the importance of design innovation, product quality improvement, and marketing strategies based on emotional and historical attachment to the club. Keywords: Consumer Behavior; Fanaticism; Merchandise; Purchase Decision; Supporter Loyalty.